Dynamic simulation study of the start-up and shutdown processes for a recompression CO2 Brayton cycle. (15th November 2022) - Wang, Xuan; Cai, Jinwen; Lin, Zhimin; Tian, Hua; Shu, Gequn; Wang, Rui; Bian, Xingyan; Shi, Lingfeng
Abstract: Recently, supercritical carbon dioxide Brayton Cycles (SCBC) have been regarded as one of the most promising next-generation power cycles owing to their high efficiency, compact components, and feasible integration. The start-up and shutdown of SCBCs are important transition stages with complex operations involving the operation of the heat source, cooling source, compressor speed, CO2 filling system, and various control valves. However, there are few related literatures, and none presents a comprehensive description of all of the operations. Consequently, in this study, detailed discussions of all of the operations during both the start-up and shutdown processes for a recompression cycle are carried out by dynamic simulation. Some keys of the operations are found to help operators achieve successful start-up and shutdown in practice. For example, to avoid wasteful charging and discharging of CO2, the variations in the fuel supply and compressor speed should be coordinated. Moreover, to avoid surges, the changes in the speeds of the two compressors should not be too different. During the shutdown process, the decrease in the fuel supply should be slower than the decrease in compressor speed to reduce the total negative work consumed by the system; the opposite is true during the start-up process. Highlights: Simulation of start-up and shutdown of recompression CO2 Brayton cycle. Detailed and comprehensive description of all of the related operations. The effects of key operations on the processes are revealed. Successful start-up and shutdown can be achieved based on the strategy.